2022
DOI: 10.1039/d1qo01675j
|View full text |Cite
|
Sign up to set email alerts
|

Cu(ii)-Catalyzed C2-site functionalization of p-aminophenols: an approach for selective cross-dehydrogenative aminations

Abstract: The site selective cross dehydrogenative aminations from precursors without preactivated C-H and N-H bonds has been challenging. Herein, a copper-catalyzed C2-site selective amination of p-aminophenol derivatives with arylamines had been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Based on controlled experiments, the authors proposed that the amination reaction may undergo a process of radical-radical crosscoupling between the phenoxyl radical 39 and the N-radical 40. In 2022, Zhao et al [24] reported a copper-catalyzed C2-site selective amination of free p-aminophenol derivatives 35 with arylamines 36 under mild conditions, using air as a terminal oxidant, and a variety of C2-site functional aminophenol derivatives 37 were obtained with 39-78% yields (Scheme 7). Interestingly, the para-benzomorpholine substituted phenol was also compatible with the reaction system for transformation into the desired C2-site selective aminated product 37a in 58% yield with oxidation of the benzomorpholine group to 4H-benzo[b] [1,4]oxazine.…”
Section: Methodsmentioning
confidence: 99%
“…Based on controlled experiments, the authors proposed that the amination reaction may undergo a process of radical-radical crosscoupling between the phenoxyl radical 39 and the N-radical 40. In 2022, Zhao et al [24] reported a copper-catalyzed C2-site selective amination of free p-aminophenol derivatives 35 with arylamines 36 under mild conditions, using air as a terminal oxidant, and a variety of C2-site functional aminophenol derivatives 37 were obtained with 39-78% yields (Scheme 7). Interestingly, the para-benzomorpholine substituted phenol was also compatible with the reaction system for transformation into the desired C2-site selective aminated product 37a in 58% yield with oxidation of the benzomorpholine group to 4H-benzo[b] [1,4]oxazine.…”
Section: Methodsmentioning
confidence: 99%
“…2), 11 dyes 12 and photographic materials, 13 and they are often used as precursors for diversification. 14 Because of their versatile structures, the synthesis of p -aminophenols has received considerable attention. However, methods for their synthesis from p -nitrophenols, 15 p -halophenols or p -haloanilines, 16 phenols or anilines 17 suffer from obvious drawbacks, namely multistep synthesis processes, harsh reaction conditions, and the need for expensive catalysts, oxidants and acids.…”
Section: Introductionmentioning
confidence: 99%